Glue septal ablation: A promising alternative to alcohol septal ablation - Sercan Okutucu (JRSM Cardiovascular Disease, 2016)
Hypertrophic cardiomyopathy (HCM) is defined as myocardial hypertrophy in the absence of another cardiac or systemic disease capable of producing the magnitude of present hypertrophy. In about 70% of patients with HCM, there is left ventricular outflow tract (LVOT) obstruction (LVOTO) and this is known as obstructive type of hypertrophic cardiomyopathy (HOCM). Cases refractory to medical treatment have had two options either surgical septal myectomy or alcohol septal ablation (ASA) to alleviate LVOT gradient. ASA may cause some life-threatening complications including conduction disturbances and complete heart block, hemodynamic compromise, ventricular arrhythmias, distant and massive myocardial necrosis. Glue septal ablation (GSA) is a promising technique for the treatment of HOCM. Glue seems to be superior to alcohol due to some intrinsic advantageous properties of glue such as immediate polymerization which prevents the leak into the left anterior descending coronary artery and it is particularly useful in patients with collaterals to the right coronary artery in whom alcohol ablation is contraindicated. In our experience, GSA is effective and also a safe technique without significant complications. GSA decreases LVOT gradient immediately after the procedure and this reduction persists during 12 months of follow-up. It improves New York Heart Association functional capacity and decrease interventricular septal wall thickness. Further studies are needed in order to assess the long-term efficacy and safety of this technique.